Implementation and evaluation of “I-Guide,” a pilot near-peer Internal Medicine mentorship program - Mahmood, Hamza; Zheng, Katina; Elias, Sarah; Sheriff, Laura; Endres, Kaitlin; Rouhani, Soroush; Malhi, Gurpreet; Khamisa, Karima (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2021)
Implication Statement: An Internal Medicine (IM) specific, near-peer mentorship program was initiated at the University of Ottawa (uOttawa) in 2017. Medical students were paired with IM resident mentors to improve career decision-making through student-oriented discussion topics. Program evaluation was completed using data from three participant cohorts and showed that the program had a positive impact on students’ career decision-making. Given the program’s flexible nature and ease of implementation, it is well suited for adaptation at other institutions.